A real world analysis of first line treatment of advanced EGFR mutated non-small cell lung cancer: A multi-center, retrospective study. (July 2022) - Lee, Chung-Shien; Ahmed, Iman; Miao, Emily; Chung, Shirley; Patel, Khilna; Kohn, Nina; Seetharamu, Nagashree
Introduction: The recently published FLAURA trial demonstrated that osimertinib has remarkable efficacy in front-line setting for non-small cell lung cancer (NSCLC). While this has transformed current practice, there are no effective treatments following progression on osimertinib. The aim of our study was to compare progression-free survival (PFS) and overall survival (OS) between patients initiated on osimertinib to those started on other EGFR TKIs. Methods: This was a multicenter, retrospective study conducted at two large academic centers. Adult patients with EGFR -mutated non-small cell lung cancer (NSCLC) who received EGFR therapy between 2014 and 2019 were included. Patients were dichotomized based on front-line TKI (osimertinib vs. other). PFS, OS, and time-to-discontinuation were evaluated. Results: One-hundred seventy-two patients were included in the final analysis. Fifty-two (30.2%) patients received osimertinib and 120 (69.8%) patients received another EGFR TKI. The PFS rates at 6, 12, and 18 months were 86.3%, 79.5%, 69.8% in the osimertinib group and 86.6%, 64.2%, 39.3% in the other EGFR TKI group, respectively (p < 0.0036).Estimated OS at 6, 12, and 18 months was similar for both groups: 94.2%, 94.2%, 80.2% and 95.7%, 93.9%, 84.1%, respectively [Adjusted HR = 0.95 (95% CI, 0.37–2.44; p < 0.9128]. Conclusion: Osimertinib demonstrated greater 12 and 18 month PFS compared to other EGFR TKIs. This finding is consistent with results of the FLAURA trial. However, unlike FLAURA, there were no differences in estimated OS between the two groups in our study. Further research to evaluate optimal sequencing strategies in the real world of first, second and third generation TKIs is needed.